Replacing Effective Spectral Radiance by Temperature in Occupational Exposure Limits to Protect Against Retinal Thermal Injury from Light and Near IR Radiation. - Madjidi, Faramarz; Behroozy, Ali (Journal of Occupational & Environmental Hygiene, 2014)
Exposure to visible light and near infrared (NIR) radiation in the wavelength region of 380 to 1400 nm may cause thermal retinal injury. In this analysis, the effective spectral radiance of a hot source is replaced by its temperature in the exposure limit values in the region of 380–1400 nm. This article describes the development and implementation of a computer code to predict those temperatures, corresponding to the exposure limits proposed by the American Conference of Governmental Industrial Hygienists (ACGIH®). Viewing duration and apparent diameter of the source were inputs for the computer code. At the first stage, an infinite series was created for calculation of spectral radiance by integration with Planck’s law. At the second stage for calculation of effective spectral radiance, the initial terms of this infinite series were selected and integration was performed by multiplying these terms by a weighting factor R(λ) in the wavelength region 380–1400 nm. At the third stage, using a computer code, the source temperature that can emit the same effective spectral radiance was found. As a result, based only on measuring the source temperature and accounting for the exposure time and the apparent diameter of the source, it is possible to decide whether the exposure to visible and NIR in any 8-hr workday is permissible. The substitution of source temperature for effective spectral radiance provides a convenient way to evaluate exposure to visible light and NIR.